Separation, characterization and quantification of phenolic compounds in blueberries and red and black currants by HPLC-DAD-ESI-MSn - Gavrilova, Verka; Kajdzanoska, Marina; Gjamovski, Viktor; Stefova, Marina (American Chemical Society (ACS), 2011)
The phenolic profile of four blueberry varieties (Vaccinium corymbosum L., cv. Toro, Legacy, Duke and Bluecrop) and two varieties (Rosenthal and Rovada) of red currants (Ribes rubrum L.) and black currants (Ribes nigrum L.) cultivated in Macedonia have been analyzed using HPLC coupled to diode-array detection and tandem mass spectrometry with electrospray ionization. A complex profile of anthocyanins, flavonols, flavan-3-ols and hydroxycinnamic acid derivatives has been assayed in acetone-acetic acid (99:1, v/v) extracts. Anthocyanins comprised the highest content of total phenolic compounds in currants (>85%) and lower and variety dependent in blueberries (35-74%). Hydroxycinnamic acid derivatives comprised 23-56% of total phenolics in blueberries and 1-6% in currants. Chlorogenic acid was the major hydroxycinnamic acid in blueberries, only in the Legacy variety, two malonyl-caffeoylquinic acid isomers were major components. Flavonols, mainly quercetin and myricetin glycosides, were a minor group, but glucosides of laricitrin and syringetin were also detected in the blueberry varieties counting for 10-34% of total flavonols. From flavan-3-ols, catechin was detected in most samples; the dimer B2 was specific for blueberries whereas epigallocatechin was detected in currants.